A Novel and Innovative Approach for Image Steganography with Chaos - Krishnaveni N; Sudhakar P (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Steganography is the art/technique of hiding message data inside a carrier file in such a way that unauthorized or unsolicited personnel is not capable of detecting the presence of data inside the carrier file. The Proposed Method provides improved security and improved high embedding capacity image steganography through the usage of Integer Wavelet Transform (IWT) and Chaotic Logistic map. Least Significant Bit technique is used to replace the bits in the coefficient of detail band. The proposed method offers lossless and unnoticeable change in the image steganography. In this paper we focus on both cryptography and steganography for better confidentiality, security and robustness. We find that the proposed algorithm has a better CMPSNR (Chaotic Logistic mapping) value averaging close to 74 after embedding the secret data, while the existing algorithms have values of around 65.